Sistem Pendukung Keputusan Penentuan Mutasi Pegawai Pada Kantor Gubernur Sumatera Utara Dengan Menggunakan Metode Additive Ratio Assessment (Aras) - Shinta Dwi Handayani (STMIK Budi Darma, 2020)
Decision Support System (SPK) is a computer-based system that can solve unstructured problems. Several methods of Additive Ratio Assessment (ARAS). The Additive Ratio Assessment (ARAS) method is a method used for ranking criteria. can be mutated tasks and / or location tasks in one central agency. Employees are very important human resources in an organization of the Republic. Employees have thoughts, encouragement, feelings, desires, status needs, educational background, age and gender heterogeneous brought into the organization. Employee transfers at the North Sumatra Governor's office are conducted at the end of each period. Employee mutations carried out for those in the North Sumatra governor's office evaluate the career of each employee. In the process of developing a decision for the transfer of employees of the North Sumatra governor's office. Problems often occur because the evaluation of the selection of employees who are transferred is very difficult because of the work performance of employees at the North Sumatra governor's office having an average rating that is almost the same and fulfills every specified criteria.